Pulmonary Parenchymal 18F-FDG Uptake on PET/MRI in Pulmonary Arterial Hypertension: A Comparative Study with Healthy Controls and Prognostic Implications - Remigiusz Kazimierczyk; Piotr M. Szumowski; Stephan G. Nekolla; Łukasz Małek; Piotr Błaszczak; Marta Kosciuk; Janusz Mysliwiec; Karol A. Kaminski (Journal of Clinical Medicine, 2026)
Background: Pulmonary arterial hypertension (PAH) is characterized by progressive vascular remodeling and right ventricular (RV) dysfunction. 18F-FDG PET/MRI may reveal metabolic alterations in the pulmonary parenchyma and vasculature. We investigated pulmonary FDG uptake in PAH versus healthy controls and its associations with hemodynamics, RV function, and clinical outcomes. Methods: Twenty-eight stable PAH patients and 12 age-matched healthy controls underwent 18F-FDG PET/MRI. Standardized uptake values (SUVs) were measured in lung parenchyma and proximal pulmonary arteries. Hemodynamic parameters were obtained via right heart catheterization; RV–PA coupling was assessed as stroke volume/end-systolic volume (SV/ESV). Twenty PAH patients underwent follow-up imaging after targeted therapy. Clinical endpoints (CEPs: death, hospitalization, disease progression) were analyzed by Kaplan–Meier and Cox regression. Results: PAH patients showed markedly elevated lung parenchymal SUV (0.405 [0.338–0.533] vs. 0.225 [0.207–0.273], p < 0.001) and proximal PA SUV (3.46 [1.95–6.89] vs. 1.48 [1.15–1.65], p < 0.001). The two metrics were uncorrelated (r = +0.105, p = 0.595). SUV PA Proximal correlated with mPAP (r = +0.551) and PVR (r = +0.517), while SUV Lung showed no hemodynamic correlations. After 24 months of therapy, RV–PA coupling improved significantly (p = 0.037); lung SUV showed a non-significant trend toward reduction (Δ = −0.10, p = 0.128). Sixteen CEPs occurred; impaired RV–PA coupling (HR = 0.04, p = 0.002), elevated mPAP (HR = 1.08, p < 0.001), and reduced RVEF (HR = 0.91, p < 0.001) were strong univariable predictors. Neither SUV metric retained independent prognostic value in multivariable analysis. Conclusions: Pulmonary parenchymal and proximal PA FDG uptake are markedly elevated in PAH. However, neither metric independently predicts hemodynamic severity or clinical outcomes, limiting their current role as reliable prognostic surrogates.